7(a-8)+19=2(a-6)

Simple and best practice solution for 7(a-8)+19=2(a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(a-8)+19=2(a-6) equation:


Simplifying
7(a + -8) + 19 = 2(a + -6)

Reorder the terms:
7(-8 + a) + 19 = 2(a + -6)
(-8 * 7 + a * 7) + 19 = 2(a + -6)
(-56 + 7a) + 19 = 2(a + -6)

Reorder the terms:
-56 + 19 + 7a = 2(a + -6)

Combine like terms: -56 + 19 = -37
-37 + 7a = 2(a + -6)

Reorder the terms:
-37 + 7a = 2(-6 + a)
-37 + 7a = (-6 * 2 + a * 2)
-37 + 7a = (-12 + 2a)

Solving
-37 + 7a = -12 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-37 + 7a + -2a = -12 + 2a + -2a

Combine like terms: 7a + -2a = 5a
-37 + 5a = -12 + 2a + -2a

Combine like terms: 2a + -2a = 0
-37 + 5a = -12 + 0
-37 + 5a = -12

Add '37' to each side of the equation.
-37 + 37 + 5a = -12 + 37

Combine like terms: -37 + 37 = 0
0 + 5a = -12 + 37
5a = -12 + 37

Combine like terms: -12 + 37 = 25
5a = 25

Divide each side by '5'.
a = 5

Simplifying
a = 5

See similar equations:

| ln(5-4x)=2x | | 10-10c=1-9x | | 2x-8(9-x)=19 | | 2(4x+4)=3(x+3) | | 12-4(x-2)=3x+1 | | 15m^2+31m=-10 | | 10m-18=200 | | 3x+3.1=8.5 | | X-27=-48 | | (10m^3-13m^2+7m+9)-(-7m^3+14m^2-2m-3)= | | -4-3x=x+4 | | (-a)(-b)(-c)/(d)= | | y-(-7)=1/7(x-(-7)) | | 3x-7(8-x)=9 | | -2x(7+3y)+6y=6 | | 15a^2+2=13a | | 3/2x=-1/8x-2 | | m-2.2= | | 5am(5-y)=5axy-7 | | 12-6x=12-6 | | (-3x^4+5x^6-5)+(-2x^5+2)-(-7x^5+7x^6+9x^4)= | | -2(7+3y)+6y=6 | | -6x-1=-6x-1 | | 3x-5(x-2)=-9+3x-11 | | R/7=1/2 | | 3x+6=3(2x+6) | | 5k^2=-18k+8 | | 3.5q-145.5=5 | | (9x^9+5x^8+5x^7-3)-(4x^9-9x^8-3x^7+4)= | | 36x^2-86x+36=0 | | 3x+8-4x+2=4x+2 | | 4=1/3(x)-7 |

Equations solver categories